Epistemologi Konstitusi Sebagai Fondasi Ilmiah Penyelenggaraan Negara di Indonesia - Putu Wahyu Widiartana; Ni Putu Ega Maha Wiryanthi; M. Arief Amrullah; Fendi Setyawan (Fakultas Hukum, Universitas Warmadewa, 2026)
This article explores the Constitution as a system of knowledge and argues that constitutional epistemology provides a scientific foundation for state governance in Indonesia. It views the 1945 Constitution not only as a legal text but as a product of historical experience and rational thought that shapes how state authority is interpreted and exercised. Using a normative legal method with statutory and conceptual approaches, this study examines how constitutional meaning is constructed and how truth claims about the Constitution are validated. The findings show that Indonesia’s constitutional practice has undergone an epistemic shift after the amendments of 1999-2002, strengthening constitutionalism, the rule of law, and judicial review. This shift underscores the importance of coherent constitutional interpretation to avoid political pragmatism and inconsistent use of power. By integrating constitutionalism and the rule of law, the article proposes a constructive framework for assessing constitutional actions not only through formal legality but also through epistemic validity. This research contributes to the discourse on constitutional knowledge and supports a more rational and principled practice of constitutional governance in Indonesia.